Erectile function, urinary continence and oncologic outcomes of neurovascular bundle sparing robot-assisted radical prostatectomy for high-risk prostate cancer: A systematic review and meta-analysis - Liu, Yang; Deng, Xian-zhong; Qin, Jiao; Wen, Zhi; Jiang, Yu; Huang, Jing; Wang, Chong-jian; Chen, Cai-xia; Wang, Li; Li, Kun-peng; Wang, Jia-hao; Yang, Xue-song (Frontiers in Oncology, 2023)
Background: The nerve-sparing (NS) effect of robot-assisted radical prostatectomy (RARP) on patients with a high-risk prostate cancer remains unclear. The objective of this study was to compare the urinary continence, erectile function and oncology outcomes of the nerve-spring and non-nerve-spring (NNS) group during RARP surgeries. Methods: We systematically searched databases including PubMed, Embase, Cochrane Library and Web of Science to identify relevant studies published in English up to December 2022. Newcastle-Ottawa Scale (NOS) was used as a quality evaluation tool to evaluate the quality of the literature parameters involved, including urinary continence, erectile function and oncology outcomes, which were compared using the Stata 15.1 software (StataSE, USA). Results: A total of 8 cohort studies involving 2499 patients were included. A meta-analysis of results showed that the NS group was beneficial to the recovery of urinary continence (RR 0.46, 95%CI 0.22, 0.96; p=0.045＜0.05) and erectile function (RR 0.32, 95%CI 0.16, 0.63; p=0.001＜0.05) 12 months after surgeries, which showed a better oncological outcome (RR 1.31, 95%CI 1.01, 1.69; p＝0.01＜0.05). Conclusions: The current study results indicate that intraoperative NS during RARP is beneficial to long-term postoperative functional recovery and tumor prognosis of patients with high-risk prostate cancers. Due to interstudy interferences, the results should be interpreted with caution.